Final analysis of a phase 1/2b study of ibrutinib combined with carfilzomib/dexamethasone in patients with relapsed/refractory multiple myeloma. Issue 3 (11th March 2020) - Chari, Ajai; Cornell, Robert F.; Gasparetto, Cristina; Karanes, Chatchada; Matous, Jeffrey V.; Niesvizky, Ruben; Lunning, Matthew; Usmani, Saad Z.; Anderson, Larry D.; Chhabra, Saurabh; Girnius, Saulius; Shustik, Chaim; et al.
Abstract: Patients with multiple myeloma (MM) inevitably relapse on initial treatment regimens, and novel combination therapies are needed. Ibrutinib is a first‐in‐class, once‐daily inhibitor of Bruton's tyrosine kinase, an enzyme implicated in growth and survival of MM cells. Preclinical data suggest supra‐additivity or synergy between ibrutinib and proteasome inhibitors (PIs) against MM. This phase 1/2b study evaluated the efficacy and safety of ibrutinib plus the PI carfilzomib and dexamethasone in patients with relapsed/refractory MM (RRMM). In this final analysis, we report results in patients who received the recommended phase 2 dose (RP2D; ibrutinib 840 mg and carfilzomib 36 mg/m 2 with dexamethasone), which was determined in phase 1. The primary efficacy endpoint was overall response rate (ORR). Fifty‐nine patients with RRMM received the RP2D (18 in phase 1 and 41 in phase 2b). These patients had received a median of three prior lines of therapy; 69% were refractory to bortezomib, and 90% were refractory to their last treatment. ORR in the RP2D population was 71% (stringent complete response and complete response: 3% each). Median duration of clinical benefit and median duration of response were both 6.5 months. Median progression‐free survival (PFS) was 7.4 months, and median overall survival (OS) was 35.9 months. High‐risk patients had comparable ORR and median PFS (67% and 7.7 months, respectively) to non–high‐risk patients, whose ORR was 73% and median PFS was 6.9 months, whereas median OS in high‐risk patients was 13.9 months and not reached in non–high‐risk patients. The most common grade ≥3 hematologic treatment‐emergent adverse events (TEAEs) were anemia and thrombocytopenia (17% each); the most common grade ≥3 non‐hematologic TEAE was hypertension (19%). In patients with RRMM treated with multiple previous lines of therapy, ibrutinib plus carfilzomib demonstrated anticancer activity within the expected efficacy range. No new safety signals were identified and the combination was well‐tolerated.